A novel homozygous mutation in WDR19 induces disorganization of microtubules in sperm flagella and nonsyndromic asthenoteratospermia - Ni, Xiaoqing (J Assist Reprod Genet, 2020)
BACKGROUND: Asthenoteratospermia with multiple morphological abnormalities in the sperm flagella (MMAF) is a significant cause of male infertility. WDR19 is a core component in the IFT-A complex and has a critical role in intraflagellar transport. However, the role of WDR19 mutations in male infertility has yet to be examined. METHODS AND RESULTS: We performed whole exome sequencing (WES) for 65 asthenoteratospermia individuals and identified a proband who carried a homozygous WDR19 (c.A3811G, p.K1271E) mutation from a consanguineous family. Systematic examinations, including CT scanning and retinal imaging, excluded previous ciliopathic syndromes in the proband. Moreover, semen analysis of this patient showed that the progressive rate decreased to zero, and the sperm flagella showed multiple morphological abnormalities. Scanning and transmission electron microscopy assays indicated that the ultrastructure of sperm flagella in the patient was completely destroyed, while immunofluorescence revealed that WDR19 was absent from the sperm neck and flagella. Moreover, IFT140 and IFT88, predicted to interact with WDR19 directly, were mis-allocated in the WDR19-mutated sperm. Notably, the MMAF subject harboring WDR19 variant and his partner successfully achieved clinical pregnancy through intracytoplasmic sperm injection (ICSI). CONCLUSIONS: We identified WDR19 as a novel pathogenic gene for male infertility caused by asthenoteratospermia in the absence of other ciliopathic phenotypes, and that patients carrying WDR19 variant can have favorable pregnancy outcomes following ICSI. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10815-020-01770-1) contains supplementary material, which is available to authorized users.